MHD mixed convection in a chamfered lid-driven cavity with partial heating - Colak, Eren; Öztop, Hakan Fehmi; Ekici, Ozgur (Pergamon-Elsevier Science Ltd, 2020)
In this study, MHD mixed convection lid-driven cavity problem is investigated to find thermal effects of chamfer on the corner of the cavity. For this purpose, open source CFD software, OpenFOAM's existing solver is modified to add Lorentz Force to the momentum equation. Simulation parameters consist of different Richardson numbers (0.01 <= Ri <= 100), Hartmann numbers (0 <= Ha <= 75), magnetic field angle values (0 degrees <= gamma <= 90 degrees), different chamfer radii (0.1 <= r * <= 0.3) and Lid Motion Direction (LMD) as positive and negative. The square cavity is partially heated from the bottom plate covering 40% of its length and the rest of the bottom plate is considered as adiabatic along with the side walls. Top plate an isothermal moving lid and its temperature is lower than the bottom plate. It is observed that chamfer presence can increase the heat transfer but effectiveness of chamfer is limited and dependent on the size of corner vortices and chamfer radius. For a square cavity, only 0.39% increase in the average Nusselt number is obtained at maximum. If there is no corner vortex, chamfer can also block the main stream and decrease heat transfer up to 11%. Lid motion direction can increase the effectiveness of the chamfer, depending on the corner vortex size and at gamma = 45 degrees, reverse lid motion direction increases average Nusselt number up to 57.2% compared to the positive lid motion direction. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: MHD flow; Mixed convection; CFD; Lorentz force; Lid-driven cavity